Pengembangan Taman Budaya Raden Saleh Sebagai Pusat Budaya Di Kota Semarang (Penekanan Arsitektur Neo-Vernakular) - Ma'adin, Saleha, Dr. Ir. Qomarun, MM, Ir. Samsudin Raidi, MSc (2015)
Taman Budaya Raden Saleh is a cultural park which was founded in 1998, which was originally named the Museum of Raden Saleh. Subsequent developments, this area is planned to be cultural area that can accommodate activities related to culture, then the name was changed to Taman Budaya Raden Saleh (TBRS), but since the economic crisis in the 1997's, cultural arts activities began to decline with decreasing the number of visitors, so many abandoned art facilities and become rundown. Assessment begins with studying the review of the Cultural Park, an overview of the theory of city and regional planning, and supported by comparative studies in Central Java Cultural Park and Taman Budaya Yogyakarta. Also conducted a review of the existing condition of Semarang and Cultural Park Raden Saleh and organizing arts and cultural development in the city. Approach to architectural design is done with the concept of Neo Vernacular Architecture of Central Java. Moreover performed functional approach, performance, technical, and contextual.